Preparation process of vulcanized polymer lithium battery positive electrode material
Patent Information
- Application Number
- CN202611052453.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,现有硫化聚合物锂电池正极材料仍存在若干不足
[0025] (1) In this invention, sublimed sulfur powder, polyacrylonitrile powder, titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon, and battery-grade acetylene black are used as precursor systems for the sulfurized polymer cathode. After drying, mixing, nitrogen-protected reaction, heat treatment, and sieving, a sulfurized polymer lithium battery cathode material is obtained. The sublimed sulfur powder and polyacrylonitrile powder form a sulfurized polymer structure under heating conditions, which transforms sulfur from a free and dispersed state into a sulfur-containing structure bound to the polymer skeleton, thereby reducing the enrichment of free sulfur and the migration of sulfur-containing species. The titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon is distributed between the sublimed sulfur powder and the polyacrylonitrile powder, which can improve the contact state of the sulfurization reaction, reduce the impact of insufficient local sulfurization on the stability of the material, and make the obtained sulfurized polymer composite cathode powder have good compositional uniformity and structural stability.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium battery cathode material technology, specifically relating to a preparation process of a sulfurized polymer lithium battery cathode material. Background Technology
[0002] With the increasing demand for high-energy-density storage devices in new energy vehicles, large-scale energy storage, and portable electronic devices, traditional lithium-ion battery cathode materials are gradually failing to meet the development requirements for higher energy densities in terms of theoretical capacity and material cost. Sulfur-containing cathode materials have attracted widespread attention due to their abundant sulfur resources, high theoretical capacity, and relatively low environmental impact. Among them, sulfurized polymer cathode materials can fix sulfur species through a polymer framework, and compared to simple sulfur-carbon composite cathodes, they have the potential to suppress the migration of soluble polysulfides, mitigate the shuttle effect, and improve cycle stability. Therefore, constructing sulfurized polymer cathode materials based on polyacrylonitrile powder and sublimed sulfur powder has become an important technological direction that balances performance improvement and cost control.
[0003] However, existing sulfurized polymer lithium-ion battery cathode materials still have several shortcomings. During polymer sulfurization, the uniformity of contact between sulfur powder and polyacrylonitrile directly affects the degree of sulfurization. If the raw materials are not sufficiently dispersed, localized free sulfur or under-sulfurized regions can easily form, leading to increased irreversible capacity loss in the first cycle and capacity decay in later cycles. Meanwhile, the bulk electronic conductivity of sulfurized polymers is limited, and relying solely on conventional conductive agents makes it difficult to form continuous transport channels within the particles. Especially under high loading and high rate conditions, cathode polarization increases significantly, and the utilization rate of active sulfur decreases. Furthermore, if a large amount of physically adsorbed sulfur remains after the sulfurization products undergo heat treatment, it will increase side reactions in subsequent electrochemical reactions, further affecting the coulombic efficiency and long-term stability of the cathode material. Summary of the Invention
[0004] To address the shortcomings of existing technologies, the present invention aims to provide a preparation process for a sulfurized polymer lithium battery cathode material, comprising the following steps:
[0005] S1. By weight, 45-60 parts of sublimed sulfur powder, 28-42 parts of polyacrylonitrile powder, 3-8 parts of titanium dioxide-supported phosphorus, nitrogen and sulfur-doped porous carbon and 4-8 parts of battery-grade acetylene black are dried and then mixed to obtain a mixture of vulcanized polymer cathode precursor.
[0006] S2. Under nitrogen protection, the mixture of vulcanized polymer cathode precursor is heated to 300-360℃ to react and obtain vulcanized products.
[0007] S3. Cool the sulfidation product to room temperature naturally, then pulverize it to obtain the pulverized sulfidation product; under nitrogen protection, heat the pulverized sulfidation product to 380-420℃ for heat treatment to obtain sulfidated polymer composite cathode powder.
[0008] S4. Sieve the sulfurized polymer composite cathode powder.
[0009] In this invention, during the preparation of the sulfurized polymer lithium battery cathode material, sublimed sulfur powder, polyacrylonitrile powder, titanium dioxide-loaded phosphorus, nitrogen, and sulfur-doped porous carbon, and battery-grade acetylene black are dried to remove adsorbed moisture from the raw materials, preventing side reactions during subsequent high-temperature processing. Mechanical mixing forms a powder interface where sublimed sulfur powder and polyacrylonitrile powder are in close contact, with the phosphorus, nitrogen, and sulfur-doped porous carbon dispersed between them. Battery-grade acetylene black fills the interparticle gaps, forming a preliminary conductive network. During the sulfurization reaction stage under nitrogen protection, the sublimed sulfur powder melts upon heating and gradually opens its ring to form sulfur-containing short-chain free radicals. Adjacent nitrile groups in the polyacrylonitrile powder undergo intramolecular cyclization to form a conjugated pyridine ring skeleton accompanied by dehydrogenation. The sulfur-containing short-chain free radicals undergo substitution and addition reactions with the active carbon sites on the conjugated skeleton, forming a short-chain sulfur structure linked by carbon-sulfur covalent bonds. This transforms sulfur from a free state into a stable structure chemically bonded to the polymer skeleton, inhibiting the release and migration of polysulfides. In the sulfidation process, phosphorus, nitrogen, and sulfur-doped porous carbon supported on titanium dioxide plays a crucial role: the porous structure of the carbon matrix adsorbs and confines molten sulfur, shortening the mass transfer distance between sulfur and polyacrylonitrile powder; the phosphorus, nitrogen, and sulfur heteroatom doping sites enhance the anchoring of sulfur-containing intermediate species due to polarity; the hydroxyl groups and titanium-oxygen coordination sites on the surface of the supported anatase titanium dioxide powder promote uniform contact and reaction between sulfur-containing species and the cyclized framework of polyacrylonitrile powder through polar adsorption. Battery-grade acetylene black maintains the continuity of electron transport between particles. After natural cooling, the sulfidation product is pulverized to break up the agglomerates formed during sulfidation and to achieve uniform particle size. During the stabilization heat treatment stage under nitrogen protection, the physically adsorbed sulfur that is not chemically bonded to the framework volatilizes and is removed as the temperature approaches its sublimation temperature. The long-chain polysulfide structure is further broken and rearranged into a more stable short-chain carbon-sulfur structure, further improving the conjugation degree of the cyclized framework of polyacrylonitrile powder and strengthening the interfacial bonding between the phosphorus, nitrogen, and sulfur-doped porous carbon supported on titanium dioxide and the sulfidated polymer. After sieving, the powder has a uniform particle size distribution. The sulfurized polymer constitutes the main active component for lithium storage, while the phosphorus, nitrogen, and sulfur-doped porous carbon supported by titanium dioxide plays a role in confinement, anchoring, and interface stabilization. Battery-grade acetylene black constitutes a conductive auxiliary network, together forming the sulfurized polymer lithium battery cathode material.
[0010] According to a preferred embodiment of the present invention, in step S1, the drying temperature is 60-80°C and the drying time is 2-4 hours.
[0011] According to a preferred embodiment of the present invention, in step S2, the reaction time is 4-8 hours after heating to 300-360°C.
[0012] According to a preferred embodiment of the present invention, in step S3, the heat treatment time at 380-420°C is 1-3 hours.
[0013] According to a preferred embodiment of the present invention, in step S4, the mesh size of the sieve is 200-400 mesh.
[0014] According to a preferred embodiment of the present invention, the preparation steps of the titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon include:
[0015] A1. By weight, add 6-12 parts of anatase titanium dioxide powder, 120-180 parts of deionized water and 20-40 parts of anhydrous ethanol to a reactor and disperse; then add 8-14 parts of phytic acid aqueous solution with a mass fraction of 68-72% and stir at 25-35℃; then add 6-10 parts of melamine and react at 80-90℃ to obtain the precursor slurry;
[0016] A2. Add 18-30 parts glucose, 10-18 parts thiourea and 160-240 parts sodium chloride to the precursor slurry and stir at 60-75℃; then dry at 80-95℃ and pre-cur at 150-170℃ to obtain a titanium dioxide-phosphorus nitrogen sulfur carbonized precursor containing salt template.
[0017] A3. The titanium dioxide-phosphorus nitrogen sulfur carbide precursor containing salt template is placed in a tube furnace and heated to 280-340℃ under a nitrogen atmosphere; then heated to 580-680℃; and naturally cooled to room temperature to obtain porous carbide containing salt template.
[0018] A4. Add the salt-containing template porous carbide to deionized water, stir and wash, and filter; then soak in 0.05-0.10 mol / L hydrochloric acid solution, and wash with deionized water until the pH of the filtrate is 6.5-7.5; then vacuum dry at 80-100℃, and then treat at 240-300℃ under nitrogen protection; pulverize and sieve.
[0019] In this invention, during the preparation of phosphorus, nitrogen, and sulfur-doped porous carbon supported on titanium dioxide, anatase titanium dioxide powder is dispersed in a dispersion medium formed by deionized water and anhydrous ethanol. The surface hydroxyl groups on the particle surface undergo surface coordination and hydrogen bonding with the phosphate groups in the phytic acid aqueous solution, anchoring and enriching phytic acid molecules on the surface of the anatase titanium dioxide powder particles. After the addition of melamine, proton transfer-based acid-base association, electrostatic interactions, and hydrogen bonding occur between the triazine cyclic amino groups in the melamine molecules and the acidic phosphate groups introduced by the phytic acid aqueous solution, forming a precursor slurry with anatase titanium dioxide powder as the inorganic core and phytic acid-melamine composite as the organic coating layer. After the addition of glucose, thiourea, and sodium chloride, glucose acts as the main carbon source coating the precursor surface, thiourea is uniformly dispersed in the system in solid form as a nitrogen and sulfur source, and sodium chloride particles act as a removable solid salt template coated by the organic components. During the drying process, deionized water and anhydrous ethanol are gradually removed, and the precursor transforms from a slurry state to a solid composite. In the pre-curing stage, glucose undergoes intermolecular dehydration condensation catalyzed by the acidic groups introduced by phytic acid. The ionic association and hydrogen bond network between phytic acid and melamine are further solidified and cross-linked. Thiourea is largely retained in the solid precursor, providing nitrogen- and sulfur-containing components for the subsequent carbonization stage. In the low-temperature treatment stage under a nitrogen atmosphere, the precursor undergoes further dehydration, condensation, and preliminary carbonization. In the high-temperature treatment stage under a nitrogen atmosphere, glucose pyrolyzes to form a carbon skeleton, melamine decomposes to release nitrogen-containing fragments and participate in the formation of nitrogen-containing structures, phytic acid is converted into phosphorus-containing oxide species and bonded to the carbon skeleton, and sulfur- and nitrogen-containing fragments generated from the thermal decomposition of thiourea are embedded in the carbon skeleton or bonded to its surface, forming a phosphorus, nitrogen, and sulfur multi-component co-doped structure. Sodium chloride remains in a solid state at this temperature, acting as a space-occupying template to restrict the dense shrinkage of the carbon skeleton. After stirring, washing, and filtering with deionized water, the sodium chloride template is dissolved and removed, leaving a porous structure. After immersion in hydrochloric acid solution, residual alkali metal ions and metal impurities on the surface can be removed. The anatase titanium dioxide powder remains stable because it is insoluble in dilute hydrochloric acid. After washing with deionized water, vacuum drying, interface treatment under nitrogen protection, pulverization, and sieving, the anatase titanium dioxide powder is finally distributed in the form of a phosphorus, nitrogen, and sulfur doped porous carbon matrix in the form of a titanium dioxide-loaded phosphorus, nitrogen, and sulfur doped porous carbon.
[0020] According to a preferred embodiment of the present invention, in step A1, the reaction time is 2-4 hours after heating to 80-90°C.
[0021] According to a preferred embodiment of the present invention, in step A2, the pre-curing time at 150-170°C is 2-4 hours.
[0022] According to a preferred embodiment of the present invention, in step A3, the time for heating to 580-680°C is 2-4 hours.
[0023] According to a preferred embodiment of the present invention, in step A4, the time for heating to 240-300°C is 1-2 hours.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) In this invention, sublimed sulfur powder, polyacrylonitrile powder, titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon, and battery-grade acetylene black are used as precursor systems for the sulfurized polymer cathode. After drying, mixing, nitrogen-protected reaction, heat treatment, and sieving, a sulfurized polymer lithium battery cathode material is obtained. The sublimed sulfur powder and polyacrylonitrile powder form a sulfurized polymer structure under heating conditions, which transforms sulfur from a free and dispersed state into a sulfur-containing structure bound to the polymer skeleton, thereby reducing the enrichment of free sulfur and the migration of sulfur-containing species. The titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon is distributed between the sublimed sulfur powder and the polyacrylonitrile powder, which can improve the contact state of the sulfurization reaction, reduce the impact of insufficient local sulfurization on the stability of the material, and make the obtained sulfurized polymer composite cathode powder have good compositional uniformity and structural stability.
[0026] (2) This invention uses anatase titanium dioxide powder, deionized water, anhydrous ethanol, phytic acid aqueous solution, melamine, glucose, thiourea, and sodium chloride to prepare titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon. Phytic acid aqueous solution and melamine form a precursor slurry, glucose provides the carbon skeleton source, thiourea provides the nitrogen and sulfur source, and sodium chloride acts as a template during the treatment process and is removed by filtration during washing, thereby forming a porous structure. This structure can disperse and confine sulfur-containing components, and the phosphorus, nitrogen, and sulfur-doped structure can enhance the interaction between the carbon skeleton and sulfur-containing species. The titanium dioxide oxide phase can provide a polar surface, thereby improving the interfacial stability of the sulfurized polymer composite cathode powder.
[0027] (3) This invention introduces battery-grade acetylene black, which can improve the conductive connection between particles in the sulfurized polymer lithium battery cathode material and reduce the polarization caused by insufficient conductivity of the sulfurized polymer. After cooling, pulverizing and heat treatment, the unstable free sulfur in the sulfurized products is reduced, and the pulverized sulfurized products are further transformed into structurally stable sulfurized polymer composite cathode powder. After sieving, the particle size distribution of the sulfurized polymer composite cathode powder is more uniform. The raw materials used in this preparation process are readily available, the steps are continuous, and the use of high-cost conductive fillers and complex sacrificial templates is avoided. While maintaining the operability of the process, the sulfur utilization rate, cycle stability and batch consistency of the sulfurized polymer lithium battery cathode material are improved. Detailed Implementation
[0028] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0029] Example 1
[0030] This embodiment provides a preparation process for a sulfurized polymer lithium battery cathode material, the steps of which include:
[0031] Step S1: Add 52.5g of sublimed sulfur powder, 35g of polyacrylonitrile powder, 5.5g of titanium dioxide-supported phosphorus, nitrogen and sulfur doped porous carbon and 6g of battery-grade acetylene black into a drying device and dry at 70°C for 3 hours to remove adsorbed water from the material. Then mix the dried material for 60 minutes until the powder color and composition are uniform to obtain a mixture of vulcanized polymer cathode precursor.
[0032] Step S2: Under nitrogen protection, the mixture of vulcanized polymer cathode precursor obtained in step S1 is heated to 330°C and reacted for 6 hours to allow the sublimed sulfur powder and polyacrylonitrile powder to undergo a vulcanization reaction, thereby obtaining the vulcanized product.
[0033] Step S3: Cool the sulfidation product obtained in step S2 to 25°C naturally, pulverize it for 10 minutes to obtain the pulverized sulfidation product; under nitrogen protection, heat the pulverized sulfidation product to 400°C for 2 hours to obtain sulfidated polymer composite cathode powder.
[0034] Step S4: Pass the sulfurized polymer composite cathode powder obtained in step S3 through a 300-mesh sieve to obtain sulfurized polymer lithium battery cathode material.
[0035] Preparation steps of titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon:
[0036] Step A1: Add 9g of anatase titanium dioxide powder, 150g of deionized water, and 30g of anhydrous ethanol to the reactor and mechanically stir for 30min to ensure that the anatase titanium dioxide powder is uniformly suspended in the mixed medium formed by deionized water and anhydrous ethanol. Then add 11g of 70% phytic acid aqueous solution and stir at 30°C for 30min to ensure that the 70% phytic acid aqueous solution fully contacts the surface of the anatase titanium dioxide powder. Then add 8g of melamine and continue stirring for 30min until the melamine is uniformly distributed in the system. Then raise the temperature to 85°C and react for 3h to obtain the precursor slurry.
[0037] Step A2: Add 24g glucose, 14g thiourea and 200g sodium chloride to the precursor slurry obtained in step A1, and stir at 67.5°C for 60min to uniformly disperse glucose, thiourea and sodium chloride in the precursor slurry; then dry at 87.5°C for 8h until the material is uniformly solid, and then pre-cured at 160°C for 3h to obtain the titanium dioxide-phosphorus nitrogen sulfur carbonized precursor containing salt template;
[0038] Step A3: The titanium dioxide-phosphorus-nitrogen-sulfur carbonization precursor with salt template obtained in step A2 is placed in a tube furnace and heated to 310°C for 1.5 h under a nitrogen atmosphere to pre-carbonize the precursor; then heated to 630°C for 3 h to form a phosphorus-nitrogen-sulfur doped carbonization system with titanium dioxide supported structure by glucose, melamine, 70% phytic acid aqueous solution and thiourea; after the treatment, it is naturally cooled to 25°C to obtain porous carbides with salt template.
[0039] Step A4: Add the salt-containing template porous carbide obtained in step A3 to 500g of deionized water and stir and wash for 30min. Filter and collect the solid. Repeat the washing with deionized water 3 times to fully dissolve the sodium chloride. Then, soak it in 200g of 0.08mol / L hydrochloric acid solution for 20min, and then wash it with deionized water until the pH of the filtrate is 7.0. Then, vacuum dry it at 90°C for 10h, and then treat it at 270°C for 1.5h under nitrogen protection. After the treatment, pulverize it and pass it through a 300-mesh sieve to obtain titanium dioxide-supported phosphorus, nitrogen and sulfur-doped porous carbon.
[0040] Example 2
[0041] This embodiment provides a preparation process for a sulfurized polymer lithium battery cathode material, the steps of which include:
[0042] Step S1: Add 45g of sublimed sulfur powder, 28g of polyacrylonitrile powder, 3g of titanium dioxide-supported phosphorus, nitrogen and sulfur-doped porous carbon and 4g of battery-grade acetylene black into a drying device and dry at 60°C for 2 hours to remove adsorbed water from the material. Then mix the dried material for 40 minutes until the powder color and composition are uniform to obtain a mixture of sulfurized polymer cathode precursor.
[0043] Step S2: Under nitrogen protection, the mixture of vulcanized polymer cathode precursor obtained in step S1 is heated to 300°C and reacted for 4 hours to allow the sublimed sulfur powder and polyacrylonitrile powder to undergo a vulcanization reaction, thereby obtaining the vulcanized product.
[0044] Step S3: Cool the sulfidation product obtained in step S2 to 25°C naturally, pulverize for 8 minutes to obtain the pulverized sulfidation product; under nitrogen protection, heat the pulverized sulfidation product to 380°C for 1 hour to obtain sulfidated polymer composite cathode powder.
[0045] Step S4: Pass the sulfurized polymer composite cathode powder obtained in step S3 through a 200-mesh sieve to obtain sulfurized polymer lithium battery cathode material.
[0046] Preparation steps of titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon:
[0047] Step A1: Add 6g of anatase titanium dioxide powder, 120g of deionized water, and 20g of anhydrous ethanol to the reactor and mechanically stir for 20min to ensure that the anatase titanium dioxide powder is uniformly suspended in the mixed medium formed by deionized water and anhydrous ethanol. Then add 8g of 68% phytic acid aqueous solution and stir at 25°C for 20min to ensure that the 68% phytic acid aqueous solution fully contacts the surface of the anatase titanium dioxide powder. Then add 6g of melamine and continue stirring for 20min until the melamine is uniformly distributed in the system. Then raise the temperature to 80°C and react for 2h to obtain the precursor slurry.
[0048] Step A2: Add 18g glucose, 10g thiourea and 160g sodium chloride to the precursor slurry obtained in step A1, and stir at 60°C for 40min to uniformly disperse glucose, thiourea and sodium chloride in the precursor slurry; then dry at 80°C for 6h until the material is uniformly solid, and then pre-cured at 150°C for 2h to obtain the titanium dioxide-phosphorus nitrogen sulfur carbonized precursor containing salt template;
[0049] Step A3: The titanium dioxide-phosphorus-nitrogen-sulfur carbonization precursor with salt template obtained in step A2 is placed in a tube furnace and heated to 280°C for 1 hour under a nitrogen atmosphere to pre-carbonize the precursor; then heated to 580°C for 2 hours to form a phosphorus-nitrogen-sulfur doped carbonization system with titanium dioxide supported structure by glucose, melamine, 68% phytic acid aqueous solution and thiourea; after the treatment, it is naturally cooled to 25°C to obtain porous carbides with salt template.
[0050] Step A4: Add the salt-containing template porous carbide obtained in Step A3 to 400g of deionized water and stir and wash for 20min. Filter and collect the solid. Repeat the washing with deionized water 3 times to fully dissolve the sodium chloride. Then, soak it in 150g of 0.05mol / L hydrochloric acid solution for 15min, and then wash it with deionized water until the pH of the filtrate is 6.5. Then, vacuum dry it at 80°C for 8h, and then treat it at 240°C for 1h under nitrogen protection. After the treatment, pulverize it and pass it through a 200-mesh sieve to obtain titanium dioxide-supported phosphorus, nitrogen and sulfur-doped porous carbon.
[0051] Example 3
[0052] This embodiment provides a preparation process for a sulfurized polymer lithium battery cathode material, the steps of which include:
[0053] Step S1: Add 60g of sublimed sulfur powder, 42g of polyacrylonitrile powder, 8g of titanium dioxide-supported phosphorus, nitrogen and sulfur doped porous carbon and 8g of battery-grade acetylene black into a drying device and dry at 80°C for 4 hours to remove adsorbed water from the material. Then mix the dried material for 80 minutes until the powder color and composition are uniform to obtain a mixture of sulfurized polymer cathode precursor.
[0054] Step S2: Under nitrogen protection, the mixture of vulcanized polymer cathode precursor obtained in step S1 is heated to 360°C and reacted for 8 hours to allow the sublimed sulfur powder and polyacrylonitrile powder to undergo a vulcanization reaction, thereby obtaining the vulcanized product.
[0055] Step S3: Cool the sulfidation product obtained in step S2 to 25°C naturally, pulverize it for 12 minutes to obtain the pulverized sulfidation product; under nitrogen protection, heat the pulverized sulfidation product to 420°C for 3 hours to obtain sulfidated polymer composite cathode powder.
[0056] Step S4: Pass the sulfurized polymer composite cathode powder obtained in step S3 through a 400-mesh sieve to obtain sulfurized polymer lithium battery cathode material.
[0057] Preparation steps of titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon:
[0058] Step A1: Add 12g of anatase titanium dioxide powder, 180g of deionized water, and 40g of anhydrous ethanol to the reactor and mechanically stir for 40 minutes to ensure that the anatase titanium dioxide powder is uniformly suspended in the mixed medium formed by deionized water and anhydrous ethanol. Then add 14g of 72% phytic acid aqueous solution and stir at 35°C for 40 minutes to ensure that the 72% phytic acid aqueous solution fully contacts the surface of the anatase titanium dioxide powder. Then add 10g of melamine and continue stirring for 40 minutes until the melamine is uniformly distributed in the system. Then raise the temperature to 90°C and react for 4 hours to obtain the precursor slurry.
[0059] Step A2: Add 30g glucose, 18g thiourea and 240g sodium chloride to the precursor slurry obtained in step A1, and stir at 75°C for 80min to uniformly disperse glucose, thiourea and sodium chloride in the precursor slurry; then dry at 95°C for 10h until the material is uniformly solid, and then pre-cured at 170°C for 4h to obtain the titanium dioxide-phosphorus nitrogen sulfur carbonized precursor containing salt template;
[0060] Step A3: The titanium dioxide-phosphorus-nitrogen-sulfur carbonization precursor with salt template obtained in step A2 is placed in a tube furnace and heated to 340°C for 2 hours under a nitrogen atmosphere to pre-carbonize the precursor; then heated to 680°C for 4 hours to form a phosphorus-nitrogen-sulfur doped carbonization system with titanium dioxide supported structure by glucose, melamine, 72% phytic acid aqueous solution and thiourea; after the treatment, it is naturally cooled to 25°C to obtain porous carbides with salt template.
[0061] Step A4: Add the salt-containing template porous carbide obtained in Step A3 to 600g of deionized water and stir and wash for 40min. Filter and collect the solid. Repeat the washing with deionized water 3 times to fully dissolve the sodium chloride. Then, soak it in 250g of 0.10mol / L hydrochloric acid solution for 25min, and then wash it with deionized water until the pH of the filtrate is 7.5. Then, vacuum dry it at 100°C for 12h, and then treat it at 300°C for 2h under nitrogen protection. After the treatment, pulverize it and pass it through a 400-mesh sieve to obtain titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon.
[0062] Comparative Example 1
[0063] The difference between this comparative example and Example 1 is that titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon is not added in step S1; otherwise, it is the same as Example 1.
[0064] Comparative Example 2
[0065] The difference between this comparative example and Example 1 is that 9g of anatase titanium dioxide powder is not added in step A1, and the material obtained is phosphorus, nitrogen, and sulfur doped porous carbon. In step S1, 5.5g of phosphorus, nitrogen, and sulfur doped porous carbon is used instead of 5.5g of titanium dioxide-loaded phosphorus, nitrogen, and sulfur doped porous carbon. The rest is the same as in Example 1.
[0066] Comparative Example 3
[0067] The difference between this comparative example and Example 1 is that 6g of battery-grade acetylene black is not added in step S1, while the rest is the same as in Example 1.
[0068] The performance of the sulfurized polymer lithium battery cathode materials provided in the above embodiments and comparative examples was tested using the following methods:
[0069] The sulfurized polymer lithium battery cathode materials prepared in Examples 1, 2, 3, 1, 2, and 3 were used as test objects. Before testing, each group of samples was dried in an 80°C vacuum drying oven for 12 hours. After cooling to 25°C, they were immediately transferred to a desiccator and sealed for later use.
[0070] For particle size D50 testing, 0.05g of sample was weighed and added to 50mL of anhydrous ethanol. The sample was ultrasonically dispersed for 3min until there was no obvious agglomeration of the powder. Then, the sample was added to the dispersion cell of the laser particle size analyzer. The shading rate was adjusted to the applicable range of the instrument. The test was repeated 3 times. The particle size corresponding to the cumulative volume fraction of 50% in the volume reference particle size distribution curve was taken as the particle size D50. The result was the average of the 3 tests.
[0071] For the specific surface area test, 0.30g of sample was weighed and placed in a sample tube. The sample was degassed under vacuum at 120°C for 6 hours. After cooling, the adsorption isotherm was tested using the nitrogen adsorption method. The linear interval of relative pressure was selected for multi-point BET calculation. Two parallel samples were tested in each group, and the average value was taken as the specific surface area.
[0072] For the initial discharge specific capacity and initial coulombic efficiency tests, the sulfurized polymer lithium battery cathode materials, battery-grade acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 80:10:10. N-methylpyrrolidone was added and stirred into a uniform slurry. The slurry was uniformly coated onto an aluminum foil current collector, pre-dried at 80°C for 2 hours, rolled, and punched into cathode sheets with a diameter of 12 mm. These sheets were then vacuum-dried at 80°C for 12 hours, controlling the active material loading in the cathode sheets to be 1.75 mg·cm³. -2 In a glove box where both water and oxygen content are below 0.1 ppm, a positive electrode is used as the working electrode, a lithium metal sheet as the counter electrode and reference electrode, and a polypropylene microporous membrane as the separator. (1 mol·L⁻¹) -1 A mixed solution of ethylene glycol dimethyl ether and 1,3-dioxolane was used as the electrolyte for lithium bis(trifluoromethanesulfonylimide), with 1% lithium nitrate additive added. Coin cells were assembled, with 5 parallel cells per group. After standing for 12 hours, constant current charge-discharge tests were conducted at 25°C, with a voltage range of 1.0-3.0V and an initial cycle current rate of 0.1C. The initial discharge capacity was recorded, and the initial discharge specific capacity was calculated based on the mass of the sulfurized polymer lithium battery cathode material. The initial coulombic efficiency was calculated as the ratio of the initial charge capacity to the initial discharge capacity.
[0073] During the 100th cycle capacity retention test, the battery, after completing the first cycle, was activated for 2 more cycles at 0.1C, and then cycled to 100 cycles at 0.5C. The discharge specific capacity of the first cycle at 0.5C and the discharge specific capacity of the 100th cycle were recorded. The capacity retention rate of the 100th cycle was calculated based on the ratio of the discharge specific capacity of the 100th cycle to the discharge specific capacity of the first cycle at 0.5C.
[0074] For the 1C rate capacity retention test, another coin cell from the same batch was taken and charged and discharged at 0.1C, 0.2C, 0.5C and 1C rates sequentially at 25°C. Each rate was cycled 5 times, and the discharge specific capacity on the 5th cycle of each rate was taken. The 1C rate capacity retention rate was calculated based on the ratio of the discharge specific capacity on the 5th cycle of 1C to the discharge specific capacity on the 5th cycle of 0.1C.
[0075] All electrochemical test results were obtained by excluding batteries with assembly defects, short circuits, or open circuits, and the average value of at least three valid parallel batteries was taken. During the testing process, the same electrolyte, separator, current collector, active material loading, and test temperature were used for the same item to ensure comparability between the examples and comparative examples.
[0076] The performance test data above are shown in Table 1.
[0077] Table 1: Performance Test Results
[0078]
[0079] As can be seen from the above, Examples 1-3, compared with Comparative Examples 1-3, solve the problems of insufficient sulfidation uniformity, poor conductivity continuity, insufficient interface stability, and significant degradation in cycle and rate performance in existing sulfurized polymer lithium battery cathode materials.
[0080] From the particle size D50, Examples 1-3 have a particle size of 7.5-8.9 μm, which is lower than Comparative Example 1's 12.6 μm. This indicates that the addition of titanium dioxide-loaded phosphorus, nitrogen, and sulfur-doped porous carbon is beneficial for suppressing the agglomeration of sulfide products and making the powder particle size more uniform. Among them, Comparative Example 1 did not add titanium dioxide-loaded phosphorus, nitrogen, and sulfur-doped porous carbon, and the particle size increased significantly. This shows that the system formed by sublimed sulfur powder, polyacrylonitrile powder, and battery-grade acetylene black alone is difficult to achieve both sulfide dispersion and powder refinement.
[0081] In terms of specific surface area, Examples 1-3 have a surface area of 56.8-66.8 m². 2 ·g -1 This is significantly higher than the 22.3m in Comparative Example 1. 2 ·g -1 This indicates that titanium dioxide-loaded phosphorus, nitrogen, and sulfur-doped porous carbon can provide an effective porous structure and confined interface, which helps the sublimated sulfur powder to fully contact with the polyacrylonitrile powder and reduces the local enrichment of free sulfur.
[0082] The initial discharge specific capacity of Examples 1-3 was 724.1-765.3 mAh·g. -1 It is significantly higher than the 602.4 mAh·g of Comparative Example 1. -1 Comparative Example 2: 686.7 mAh·g -1 Compared with Comparative Example 3, 631.5 mAh·g -1 This indicates that the utilization rate of active sulfur is improved when complete titanium dioxide-loaded phosphorus, nitrogen, and sulfur-doped porous carbon is used in conjunction with battery-grade acetylene black. In Comparative Example 2, the initial discharge specific capacity decreased after replacing titanium dioxide-loaded phosphorus, nitrogen, and sulfur-doped porous carbon with phosphorus, nitrogen, and sulfur-doped porous carbon, indicating that the polar interface provided by the titanium dioxide oxide phase promotes the dispersion and reaction utilization of sulfur-containing species.
[0083] The initial coulombic efficiency of Examples 1-3 was 92.1-93.8%, higher than that of Comparative Example 1 (86.2%), Comparative Example 2 (89.5%), and Comparative Example 3 (88.1%), indicating that the present invention can reduce irreversible side reactions in the first cycle and improve the electrochemical reversibility of the sulfurized polymer cathode structure. In terms of cycle stability, the capacity retention rate of Examples 1-3 after 100 cycles was 88.7-91.0%, significantly higher than that of Comparative Example 1 (72.7%), Comparative Example 2 (83.1%), and Comparative Example 3 (76.9%), indicating that the porous confinement of phosphorus, nitrogen, and sulfur doped porous carbon supported on titanium dioxide, the phosphorus, nitrogen, and sulfur doping sites, and the polar surface of titanium dioxide can jointly reduce the migration of sulfur-containing species and stabilize the sulfurized polymer interface. In contrast, the capacity retention rate of Comparative Example 3 decreased after the addition of battery-grade acetylene black, indicating that relying solely on phosphorus, nitrogen, and sulfur doped porous carbon supported on titanium dioxide is insufficient to establish a sufficient interparticle conductive network.
[0084] In terms of rate performance, the 1C rate capacity retention of Examples 1-3 was 78.4-82.6%, which was significantly higher than that of Comparative Example 1 (58.6%), Comparative Example 2 (70.2%), and Comparative Example 3 (61.4%). This further proves that the present invention improves the confinement of sulfur-containing species and interfacial reactions by loading phosphorus, nitrogen, and sulfur-doped porous carbon with titanium dioxide, and improves the continuity of electron transport by using battery-grade acetylene black, so that the sulfurized polymer lithium battery cathode material can still maintain a high capacity output at a high rate.
[0085] Therefore, Examples 1-3, compared to Comparative Examples 1-3, demonstrate that the present invention does not rely solely on the single effect of porous carbon or conductive carbon black. Instead, it achieves this through the synergistic effect of titanium dioxide-loaded phosphorus, nitrogen, and sulfur-doped porous carbon and battery-grade acetylene black, thereby simultaneously improving powder dispersibility, active sulfur utilization, initial coulombic efficiency, cycle stability, and rate performance. This effectively solves the technical problems of insufficient conductivity, poor interface stability, low utilization of sulfur-containing species, and rapid cycle capacity decay in existing sulfurized polymer lithium battery cathode materials.
Claims
1. A preparation process for a sulfurized polymer lithium battery cathode material, characterized in that, Includes the following steps: S1. By weight, 45-60 parts of sublimed sulfur powder, 28-42 parts of polyacrylonitrile powder, 3-8 parts of titanium dioxide-supported phosphorus, nitrogen and sulfur-doped porous carbon and 4-8 parts of battery-grade acetylene black are dried and then mixed to obtain a mixture of vulcanized polymer cathode precursor. S2. Under nitrogen protection, the mixture of vulcanized polymer cathode precursor is heated to 300-360℃ to react and obtain vulcanized products. S3. Cool the sulfidation product to room temperature naturally, then pulverize it to obtain the pulverized sulfidation product; under nitrogen protection, heat the pulverized sulfidation product to 380-420℃ for heat treatment to obtain sulfidated polymer composite cathode powder. S4. Sieve the sulfurized polymer composite cathode powder.
2. The preparation process of the sulfurized polymer lithium battery cathode material according to claim 1, characterized in that, In step S1, the drying temperature is 60-80℃ and the drying time is 2-4 hours.
3. The preparation process of the sulfurized polymer lithium battery cathode material according to claim 1, characterized in that, In step S2, the reaction time is 4-8 hours after heating to 300-360℃.
4. The preparation process of the sulfurized polymer lithium battery cathode material according to claim 1, characterized in that, In step S3, the heat treatment time at 380-420℃ is 1-3 hours.
5. The preparation process of the sulfurized polymer lithium battery cathode material according to claim 1, characterized in that, In step S4, the sieve mesh size is 200-400 mesh.
6. The preparation process of the sulfurized polymer lithium battery cathode material according to any one of claims 1-5, characterized in that, The preparation steps of the titanium dioxide-supported phosphorus, nitrogen, and sulfur-doped porous carbon include: A1. By weight, 6-12 parts of anatase titanium dioxide powder, 120-180 parts of deionized water and 20-40 parts of anhydrous ethanol are added to a reactor and dispersed; then 8-14 parts of phytic acid aqueous solution are added and stirred at 25-35℃; then 6-10 parts of melamine are added and the temperature is raised to 80-90℃ to react, and a precursor slurry is obtained. A2. Add 18-30 parts glucose, 10-18 parts thiourea and 160-240 parts sodium chloride to the precursor slurry and stir at 60-75℃; then dry at 80-95℃ and pre-cur at 150-170℃ to obtain a titanium dioxide-phosphorus nitrogen sulfur carbonized precursor containing salt template. A3. The titanium dioxide-phosphorus nitrogen sulfur carbide precursor containing salt template is placed in a tube furnace and heated to 280-340℃ under a nitrogen atmosphere; then heated to 580-680℃; and naturally cooled to room temperature to obtain porous carbide containing salt template. A4. Add the salt-containing template porous carbide to deionized water, stir and wash, and filter; then soak in hydrochloric acid solution, and wash with deionized water until the pH of the filtrate is 6.5-7.5; then vacuum dry at 80-100℃, and then treat at 240-300℃ under nitrogen protection; pulverize and sieve.
7. The preparation process of the sulfurized polymer lithium battery cathode material according to claim 6, characterized in that, In step A1, the reaction time is 2-4 hours after heating to 80-90℃.
8. The preparation process of the sulfurized polymer lithium battery cathode material according to claim 6, characterized in that, In step A2, the pre-curing time at 150-170℃ is 2-4 hours.
9. The preparation process of the sulfurized polymer lithium battery cathode material according to claim 6, characterized in that, In step A3, the treatment time for heating to 580-680℃ is 2-4 hours.
10. The preparation process of the sulfurized polymer lithium battery cathode material according to claim 6, characterized in that, In step A4, the temperature is raised to 240-300℃ and the treatment time is 1-2 hours.